2011
DOI: 10.1097/aln.0b013e31820bfc81
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension during Fluid-restricted Abdominal Surgery

Abstract: In this model of abdominal surgery in which clinical conditions were imitated as close as possible, treatment of perioperative hypotension with norepinephrine had no adverse effects on microcirculatory blood flow or tissue oxygen tension in the intestinal tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 29 publications
(37 reference statements)
1
22
1
Order By: Relevance
“…Furthermore, using an experimental model of abdominal surgery, Hiltebrand et al . found that treatment of hypotension with norepinephrine had no adverse effects on microcirculatory perfusion or tissue oxygen tension in the intestinal tract, proving that administering low to moderate doses of norepinephrine to increase perioperative blood pressure does not adversely affect peripheral tissue perfusion [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using an experimental model of abdominal surgery, Hiltebrand et al . found that treatment of hypotension with norepinephrine had no adverse effects on microcirculatory perfusion or tissue oxygen tension in the intestinal tract, proving that administering low to moderate doses of norepinephrine to increase perioperative blood pressure does not adversely affect peripheral tissue perfusion [35]. …”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, however, vasopressor therapy and arterial lactate were similar in the SSC- and nSSC-groups. Recently, the administration of norepinephrine in pigs to achieve a mean arterial pressure of 75 mmHg compared with 60 mmHg in the control group did not reduce hepatic arterial blood flow, hepatic venous oxygen saturation, or mesenterial lactate concentration [39]. Furthermore, increasing norepinephrine to achieve a higher mean arterial pressure in vasodilatory shock after cardiac surgery or sepsis did not reduce intestinal mucosal perfusion, tissue oxygenation, or microvascular flow [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…70 However, several animal studies suggest that treatment of intraoperative hypotension with norepinephrine does not cause any reduction of gut blood flow in the presence of normovolemia. 71,72 An ideal fluid regimen for major procedures, including esophageal surgery, is individualized and optimizes cardiac output and oxygen delivery while avoiding excessive fluid administration. There is some evidence that fluid therapies designed to achieve individualized and specific flow-related hemodynamic endpoints such as stroke volume or cardiac index (collectively referred to as goal-directed fluid therapy) may provide a superior alternative to fixed regimens or those based on static measures of cardiac filling, such as central venous pressure, which do not predict fluid responsiveness or correlate with circulating blood volume after transthoracic esophagectomy.…”
Section: Fluids Inflammation and The Glycocalyxmentioning
confidence: 99%